PENGARUH TOTAL QUALITY MANAGEMENT (TQM), TURN OVER INTENTION DAN LOCUS OF CONTROL TERHADAP KINERJA KARYAWAN PADA RSJ. “PUTI BUNGSU” PADANG - Yulihardi, Yulihardi (Eko dan Bisnis: Riau Economic and Business Review, 2018)
The problem in this research is "Employee Performance RSJ. “Puti Bungsu” Padang The research title is the influence of Total Quality Management (TQM), Turn Over Intention and Locus Of Control on Employee Performance. This study aims to reveal, the Influence of Total Quality Management (TQM), Turn Over Intention, and Locus Of Control together to Employee Performance RSJ. “Puti Bungsu” Padang. Total Quality Management (TQM) Influence, Turn Over Intention, and Locus Of Control partially on Employee Performance. The method used in this research is survey method. With the total population of the sample (Total Population) amounted to 91 people. The result of the research is regression equation Y = 933 + 0,227 X1 - 0,253 X2. + 0.350 X3, Total Quality Management (TQM) with sig value. 0.032, Turn Over Intention sig value. 0.010 and Locus Of Control sig value. 0.007 <0.005. Adjusted R square 0,543. The conclusion from the research that Hypothesis partially and simultaneously from Total Quality Management (TQM) variable, Turn Over Intention and Locus Of Control proved to have positive and significant influence to Employee Performance of RSJ. “Puti Bungsu” Padang with contribution 54,90% with Locus Of Control as the most dominant variable. Suggestions To focus more on improving the Turn Over Intention and Locus Of Control variables with respect to the indicators